2016
DOI: 10.17795/ijcp-6360
|View full text |Cite
|
Sign up to set email alerts
|

The Islamic Perspective of Spiritual Intervention Effectiveness on Bio-Psychological Health Displayed by Gene Expression in Breast Cancer Patients

Abstract: BackgroundDuring the last two decades, there have been spiritual/religious interventions in cancer patients to prevent or treat a range of physical problems, including managing chronic pain, coping with the disease, boosting hope and mental health. Although societies are of different faiths and belief systems, what they all share is spirituality.ObjectivesUpon this we put forward the hypothesis of changes in gene receptor expressions as a result of spiritual intervention for the first time in the world.Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
0
24
0
3
Order By: Relevance
“…Results of this review found that the majority of Middle Eastern research on spirituality and health has been conducted in either Iran or Jordan. Only two studies were found that utilised an experimental/interventional design (Moeini et al 2016;Hosseini et al 2016) and both of these were conducted in Iran. This lack of interventional research on spirituality and health is reflected globally (Jim et al 2015;Moreira-Almeida et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Results of this review found that the majority of Middle Eastern research on spirituality and health has been conducted in either Iran or Jordan. Only two studies were found that utilised an experimental/interventional design (Moeini et al 2016;Hosseini et al 2016) and both of these were conducted in Iran. This lack of interventional research on spirituality and health is reflected globally (Jim et al 2015;Moreira-Almeida et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, this review highlighted the number of studies that have investigated the relationship between spirituality and quality of life (Al-Natour et al 2017;Cruz et al 2017;Jafari et al 2014b), similar to trends in other regions (De Bernardin Gonçalves et al 2017). Two of the studies included in this review were randomized control trials that tested the effect of Islam-based spiritual interventions and demonstrated positive effects on spiritual wellbeing (Moeini et al 2016) and on biopsychological health, as measured by gene expressions in blood samples (Hosseini et al 2016). However, the study by Hosseini et al (2016) was limited in terms of methodology and analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations